Analysis of the foreign exchange market issues in the Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
Many types of structures emerged during the period of transformation of Kazakhstan’s economy into a market economy, which later became the integral part of market economy. One such element is the foreign exchange market. Foreign Exchange Market of the Republic of Kazakhstan is one of the main segments of the financial market, which determines the short-term and long-term economic development. Its formation began since independence and its development continues to this day. The state of the foreign exchange market is one of the main factors determining the long-term development prospects of domestic and international economic relations of the Republic of Kazakhstan. Therefore, determination of development dynamics and identification of issues related to foreign exchange market and finding solutions for them can help to ensure a stable economic growth. To sum up, the article aims to analyze the current state of the foreign exchange market of the Republic of Kazakhstan, describe the specific features of the market and identify the problems its development process.
Keywords: Foreign Exchange Market of the Republic of Kazakhstan; the exchange rate derivatives; the devaluation.